Designing Cooperative Covering Strategy for Intercepting a Highly Maneuvering Target. Issue 3 (2022) - Guo, Ziwei; Xu, Tao; Zhang, Zhao; Duan, Zhisheng
Abstract: In this paper, a novel guidance strategy considering the input saturation and angle constraint is developed for missiles to deal with the cooperative interception problem. Taking the upper bound of the maneuverability of the target as a prior knowledge, a new reachable set is derived to enhance the practicality. Moreover, the virtual targets of the new reachable set are obtained. Based on the new reachable set, each missile is guided to its virtual target until successful interception is achieved, which means the virtual targets coincide with the real target. Numerical simulation results are provided to illustrate the effectiveness of the proposed strategies.